Phase II study of nimotuzumab (TheraCim‐hR3) concurrent with cisplatin/radiotherapy in patients with locally advanced head and neck squamous cell carcinoma. Issue 5 (5th February 2021) - Ang, Mei‐Kim; Montoya, Jose Enrique; Tharavichitkul, Ekkasit; Lim, Cindy; Tan, Terence; Wang, Lan Ying; Wee, Joseph; Soong, Yoke‐Lim; Fong, Kam‐Weng; Ng, Quan Sing; Tan, Daniel Shao‐Weng; Toh, Chee‐Keong; et al.
Abstract: Background: The efficacy of a combination of nimotuzumab, a humanized monoclonal antibody to the epidermal growth factor receptor, with chemoradiation in locally advanced head and neck squamous cell carcinoma (HNSCC) was evaluated in a phase II study. Methods: Patients with stage III/IV HNSCC received 3‐weekly cisplatin 100 mg/m 2 for three cycles and weekly nimotuzumab 200 mg for 8 weeks concurrently with radiotherapy. Primary endpoint was best overall response (BOR) and secondary endpoint was progression‐free survival (PFS). Results: Thirty‐seven patients were included; the majority were Chinese (76%), male (89%), and had stage IVA/IVB HNSCC (92%). BOR of complete and partial response was seen in 22/37 (59%) and 10/37 (27%) patients, respectively. Median PFS was 17.5 months (95% CI: 11.1–54.5) and 3‐year PFS was 40.4% (95% CI: 24.3–55.9). The frequency and type of adverse events observed were similar to standard chemoradiation. Conclusion: The combination of nimotuzumab with cisplatin and radiotherapy was safe and achieved high response rates in HNSCC.